Penerapan Pemasaran Digital dalam Peningkatan Penjualan UMKM Peralatan Tidur di Platform Online - Aditya Hidayatus Sofyan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This study aims to analyze the implementation of digital marketing in increasing sales of small and medium enterprises (SMEs) in the bedding equipment sector on online platforms. The background of this research is driven by the high level of competition in marketplaces and the need for business actors to optimize digital marketing strategies to remain competitive. The research method used is Participatory Action Research (PAR), combined with SWOT analysis to identify business conditions comprehensively. Data collection techniques were carried out through direct observation of production and marketing activities. The results show that the implementation of digital marketing through marketplaces and social commerce can expand market reach, increase sales volume, and enhance the business actor’s understanding of managing online marketing strategies. In addition, product content optimization, the use of promotional features, and customer service play an important role in increasing consumer trust and purchase decisions. However, challenges such as high advertising costs and frequent changes in platform policies were also identified. Overall, this study concludes that well-planned and efficient digital marketing strategies can improve competitiveness, profitability, and business sustainability of SMEs in the digital era.